Analysis of the Bengkalis Regency Government's 'Bermasa' Special Financial Aid (BKK) Policy to Improve the Quality and Efficiency of Government Services - Pratama, Adrian Irnanda; Bustami, Bustami; Rosa, Nageeta Tara (Inovbiz: Jurnal Inovasi Bisnis, 2024)
This study aims to analyze the BKK "Bermasa" policy with a focus on improving the quality of services and efficiency of government administration at the village level. This research uses a qualitative approach with a policy analysis method. Data were collected through interviews with relevant stakeholders, analysis of policy documents, and observation of policy implementation in the field. Analysis of the BKK "Bermasa" policy shows positive changes in village government administration. The implementation of this program has successfully improved service quality through the application of technology, active community participation, and empowerment of village officials. In addition, there is efficiency in village financial management and development planning. The Bengkalis Regency Government's BKK "Bermasa" policy has successfully contributed positively to improving the quality and efficiency of government services at the village level. The findings provide recommendations for local governments and related parties to strengthen policies and support the sustainability of similar programs in the future